Construction of Single mother Blogger towards Attached Negative Label - Fatimah, Anggun Nadia; Nirmalasari, Andi; Puspitaningrum, Deby; Erawaty, Dyah Permana; Lumeta, Putri Neva (JURNAL KOMUNIKASI INDONESIA, 2019)
This article is intended to understand how single mother bloggers construct the single mother blogger constructs the acceptance of negative labels given by society. The negative label was inherent in women who held the status of single mother. This study was compiled based on the results of in-depth interviews conducted by researchers on the single mother bloggers and supported by a review of the blog contents written by the single mother bloggers. The research method used in this journal is hollistic single case study design with constructivism paradigm. Social interactions between the single mothers and their surrounding environment or a supporting system is emphasized in this study. An internal factor of the single mothers’ intrapersonal communication and external factor of interpersonal communication between the single mothers and supporting system, such as family, community, close friends or even people in the digital world who give positive comments, has a self-healing mechanism. The single mother bloggers used this to shape a new reality on the single mother label.